The beta Human Chorionic Gonadotropin (hCG) levels in the vaginal washing fluid as a predictor of Premature Rupture of Membrane (PROM) - Danny Aguswahyudi; Ketut Suwiyoga; I Ketut Surya Negara; I Wayan Megadhana; I Nyoman Bayu Mahendra; I Gusti Putu Mayun Mayura; Made Bagus Dwi Aryana (Intisari Sains Medis, 2022)
Background: Several biomarkers have been investigated as predictors of Premature rupture of membrane (PROM), but these biomarkers have not been applied in clinical practice due to their high cost and complexity. Beta-HCG is thought to be an easy, cost-effective and promising predictor of PROM in clinical practice. This study aims to determine the relationship between beta-hCG level in vaginal washing fluid with the PROM and the cut-off value of beta-hCG level in vaginal washing fluid in predicting the incidence of PROM.Methods: This diagnostic study was conducted in the Sanglah General Hospital, Denpasar, from May to July 2020. The subjects involved in this study are all pregnant women with gestational age ?24 weeks who came with complaints of vaginal discharge and were treated in the delivery room of the Emergency Ward, Sanglah General Hospital. The beta-HCG level was evaluated using the immunoassay method and the ROC curve analysis was performed to determine the beta-hCG level in vaginal washing cut-off point that can predict the incidence of PROM. Data were analyzed using SPSS version 22 for Windows.Results: Thirty-five subjects who met the inclusion and exclusion criteria were involved in this study. The cut-off value of beta-hCG vaginal washing fluid to predict PROM obtained in this study was 118.1 mIU/ml with sensitivity of 95.83%, specificity of 81.81%, PPV of 92.00%, NPV of 90.00%, and accuracy of 91.43% (AUC: 0.947; 95%CI: 0.870-1.000; p<0.001).Conclusion: Beta-hCG level in the vagina washing fluid can be used as a fast and non-invasive predictor of PROM in pregnant women.